Effectiveness of air pollution index to overcome air pollution in urban area / Rashdan Munir Badrul - Badrul, Rashdan Munir (2021)
Air pollution has been an ongoing problem in many countries in the Southeast Asian region, with Malaysia being one of the worst affected countries. It is really bad that the country is leading the world in unfavourable statistics. Following the recent outbreak, Malaysia has risen to the top of the list of nations with the worst levels of global air pollution. World Air Quality Index (WAQI) conducted an observational search for air pollution index (API). One of the reasons everything happened was it is all because of human being and others contributor that may harm the environmental. This has led to many effects to environmental that may be fatal to people that are occupied in the area. Peoples are currently facing major obstacles related to their living environment. This study is to identify effectiveness of air pollution index to overcome air pollution in urban area. There are three research objectives related to the purpose of the study. Firstly, it is to determine causes of air pollution in urban area in Malaysia. Second, it is also to analyse in detail regarding air pollution index in Malaysia. Third, it is also to identify how air pollution index can reduce air pollution in urban area. The quantitative method was chosen as the research tool for this study. It is done by handing out questionnaires to respondents in the case study region. This research analyses all the data given by respondents using a descriptive analysis, charts and also table. All of this test was fully analysing by tools of Microsoft Office Excel. Simply put, this study will help everyone increase their awareness regarding air pollution in urban area and also the awareness of existence and function of Air Pollution Index (API).